LEGOfied building blocks as media - Taylor, Nicholas; Ingraham, Chris (College teacher) (Bloomsbury Academic, 2020)
LEGOfied draws from a number of distinct theoretical backgrounds and disciplines in media studies to examine the practices and identities that constitute LEGO fandom, in order to articulate the ways LEGO functions as material media"--